Analisis Kecacatan dalam Proses Pembuatan Tahu Sumedang Pada CV. X dengan Pendekatan Seven Tools dan New Seven Tools - Rizal, Samsul; Aryati Rakhmasari, Aster; Melati, Meisya; Ambry, Kiki; Evionita, Patricia; Adriel, Stephanie (International Forum of Researchers and Lecturers, 2024)
The production of tofu is vulnerable to deficiencies stemming from issues such as diminished worker attentiveness, subpar raw materials, and ambiguous operational protocols. Employing the seven traditional tools and additional new methods, this study scrutinized these shortcomings. The outcomes indicate that these variables exert a notable influence on product quality. These discoveries establish a foundation for pinpointing areas of enhancement to elevate the efficiency and quality of the tofu production process.